2018
DOI: 10.5664/jcsm.6882
|View full text |Cite
|
Sign up to set email alerts
|

The MSLT is Repeatable in Narcolepsy Type 1 But Not Narcolepsy Type 2: A Retrospective Patient Study

Abstract: In a clinical setting, a positive MSLT for narcolepsy is a more reproducible and stable feature in NT1 than NT2. The retrospective design of this study hinders interpretation of these data, as there are many different, and possibly opposing, reasons to repeat a MSLT in NT1 versus NT2 (ie, ascertainment bias). Additional systematic MSLT repeatability studies independent of confounds are ideally needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…Ruoff et al. () performed a study closer to ours, looking specifically at type‐1 and type 2 narcoleptics. These authors showed again a much greater variability of results at one repeated MSLT in type‐2 narcoleptics, who changed to idiopathic hypersomnia or to a negative MSLT 26% and 57% of the time, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Ruoff et al. () performed a study closer to ours, looking specifically at type‐1 and type 2 narcoleptics. These authors showed again a much greater variability of results at one repeated MSLT in type‐2 narcoleptics, who changed to idiopathic hypersomnia or to a negative MSLT 26% and 57% of the time, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Rather, it may be another indication that the MSLT does not optimally classify hypersomnolent patients. The MSLT is normal in a substantial group of patients with symptoms of IH (Vernet & Arnulf, ) or problematic sleepiness (Pizza et al., ), and has poor test–retest reliability in several hypersomnolence disorders (Ruoff et al., ; Trotti, Staab, & Rye, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a surrogate for hypocretin deficiency, the current PSG/MSLT protocol plus cataplexy is sufficient to diagnose NT1 in most cases. The retest reliability of the PSG/MSLT for NT1 is high at 78%–81.3% [ 8 , 9 ].…”
Section: Challenges With Current Classificationmentioning
confidence: 99%
“…Thus, the second reason for lumping NT2 and IH without long sleep time springs from the poor retest reliability of MSLT for IH or NT2 diagnosis. Patients initially diagnosed with these disorders who undergo repeat testing will frequently change the diagnosis, either because of a change in SOREMs or a change in sleep latency [ 8 , 9 , 39 ]. This may be because of inconsistent MSLT testing protocols, unstable symptom characteristics, and/or that number of SOREMs on MSLT is not a stable feature of these disorders.…”
Section: International Classification Of Sleep Disorders—ideas For Thmentioning
confidence: 99%